Stability of difference rational systems - Khusainov, D. Ya.; Shevelenko, E. E. (Ukrains’kyi Matematychnyi Zhurnal, 1999)
For systems of difference equations with rational functions on the right-hand sides represented in a unified vector matrix form, we obtain stability conditions and calculate a value of the radius of a disk for the domain of asymptotic stability on the basis of the second Lyapunov method.